UK and European heatwave 2025 - Bird,J; Clarke,B; Konstantinoudis,G; Otto,F (Grantham Institute, Imperial College London, 2025)
This background briefing covers evidence on the heatwave that affected the UK and Europe in June-July 2025. It also shares evidence on the impact of climate change on heatwaves, how heatwaves affect the economy, public attitudes towards heatwaves and what is being done to protect people in the UK.